Promosi Kesehatan Untuk Meningkatkan Pengetahuan Dan Keterampilan Ibu Hamil Dalam Mengatasi Mual Muntah Pada Kehamilan Di Tiyuh Makarti Kecamatan Tumijajar Kabupaten Tulang Bawang Barat - Ristiyana, Septi; Aditia, Dita Selvia; Destri, Yuhelva; Wahyuni, Iin (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
Nausea and vomiting is a common complaint made during early pregnancy, but the result of underestimating the feeling of nausea and vomiting felt during pregnancy can objectively impact the fetus being born with LBW. For this reason, to minimize the occurrence of pathological nausea and vomiting, it is necessary to provide antenatal care. Pregnant women are advised to undergo antenatal check-ups 4 times, namely in each trimester, while in the last trimester twice. The benefits of antenatal care are very large because it can identify various risks and complications of pregnancy so that pregnant women can be directed to make referrals to hospitals (Manuaba, 2011). Complementary therapy is a method of dealing with disease that is carried out as a support for conventional medical treatment or as another treatment option outside conventional medical treatment (Rufaida, Lestari and Sari, 2018). Acupressure at pericardium point 6 produces good evaluations in mothers who experience nausea and vomiting in the mild and moderate categories (Maheswara et al., 2020). Based on the results of a preliminary survey conducted by interviews with 20 pregnant women in Tribe 3 Tiyuh Makarti, Tumijajar District, West Tulang Bawang Regency in 2021, as many as 18 people (80%) were unable to do acupressure to reduce nausea and vomiting. This shows that only 2 people (20%) of pregnant women can do acupressure to reduce nausea and vomiting. The aim of this community service is to provide education to pregnant women to be able to perform acupressure during pregnancy to treat nausea and vomiting. The community service method is carried out through lectures and direct demonstrations for pregnant women. The materials used in this community service were counseling materials, leaflets and demonstration tools. Participants in the activity were 20 pregnant women. There were enthusiastic participants when the activity took place. Participants know the benefits and methods of acupressure. Pregnant women should continue to apply acupressure to reduce nausea and vomiting, and families should provide motivation and encouragement to pregnant women to reduce nausea and vomiting.